Pembuatan Aplikasi Sistem Pencatatan Transaksi Penjualan Pulsa - Alfatah, Dhika; Sukindro , Afif; Rahayu , Novi (CV. Generasi Insan Rafflesia, 2023)
Many new operators have sprung up offering such cheap tariffs with better quality and confidently stating that it is their products that are felt to be most needed by the public. The recording of each transaction is done manually, which records every transaction made on a piece of paper, and the calculation is still done manually. manually by using this calculator which causes the old system to become less effective and efficient.It can be concluded from the formulation of the problem in this system is how to complete credit sales transactions manually. The purpose of making this thesis is to create a system program to calculate credit sales for purchases of goods and sales and purchase transactions, these transactions will automatically be recorded in the database.The data collection method used in conducting this research is through primary data (interviews, observations) and secondary data (documents). From the results of the design and manufacture of the application, it can be interpreted that the application for recording DAPT pulse sales transactions is implemented in a system with the availability of a computerized database.